Jenis dan Konsentrasi Tanah Pengelantang untuk Menurunkan Prekursor Senyawa 3-MCPDE dan GE pada Pemucatan CPO - Kartika Sari; Nur Wulandari; Azis Boing Sitanggang; Nuri Andarwulan (Institut Pertanian Bogor, 2023)
Refined palm oil contains contaminants such as 3-monochloropropane diol ester (3-MCPDE) and glycidyl ester (GE) which are formed from diacylglycerol (DAG) and chloride (Cl) as precursors during processing. There is a need to control the levels of precursors especially during the bleaching stage using selected bleaching earth (BE). Reducing the number of precursors after the bleaching stage will minimize the formation of 3-MCPDE and GE in bleached palm oil (BPO) for the next refinery stage. The research consisted of three stages: (1) characterization of raw materials consisting of CPO, BE types 1, 2, 3, 4, and 5; (2) study on the effect of BE type; and (3) study on the concentration effect of selected BE for reducing DAG and Cl by chemical analysis of oil quality. The results showed that degummed palm oil (DPO) contained DAG of 6.70%, free fatty acid 5.66%, carotene 424.31 mg/kg, P 20.30 mg/kg, and Fe <0.021 mg/kg. The five types of BE have different physicochemical properties on which the effect will be seen on BPO. The second stage results showed that BE-4 was selected as the most potential BE. Using BE-4 of 2.5% was proven to reduce total Cl as 3-MCPDE precursors in the resulted BPO sample. The Cl level decreased to 3.05 mg/kg with the largest decrease percentage of 55.80% compared to DPO sample. BE-4 concentration of 2.5% has been able to withstand and prevent the increase of DAG as a precursor to GE contaminants during bleaching process. Keywords: 3-monokloropropanadiol ester, chloride, diacylglycerol, glycidyl ester, palm oil